Effects of co-players' identity and reputation in the public goods game - Waldir M. Sampaio; Ana Luísa Freitas; Gabriel G. Rêgo; Leticia Y. N. Morello; Paulo S. Boggio (Scientific Reports, 2023)
Abstract Players’ identity and their reputation are known to influence cooperation in economic games, but little is known about how they interact. Our study aimed to understand how presenting pre-programmed co-players’ identities (face photos; names) along with their previous cooperation history (reputation) could influence participants’ cooperative decisions in a public goods game. Participants (N = 759) were allocated to one of six experimental groups: (i) control (no information); (ii) only reputation (neutral, free-rider, or cooperative); (iii) only face; (iv) face with reputation; (v) only name; (vi) name with reputation. In the reputation group, cooperation significantly decreased when free-riders were playing and significantly increased when they were cooperators. Person’s identity affected cooperativeness only when combined with reputation: face photo mitigated the negative effect of the free-rider reputation, while name identity mitigated any significant effect expected for reputation. Our study suggests a hierarchy: reputation changes cooperation, but a person's identity can modulate reputation.